Morphological features of basal membrane of stratified squamous epithelium and underlying stroma in cervical intraepithelial neoplasias and cancer of the uterine cervix - Oksana M. Pliten (Kazimierz Wielki University, 2015)
Pliten O. N. Морфологічні особливості базальної мембрани багатошарового плоского епітелію і підлягаючої строми при цервікальних інтраепітеліальних неоплазіях та раку шийки матки = Morphological features of basal membrane of stratified squamous epithelium and underlying stroma in cervical intraepithelial neoplasias and cancer of the uterine cervix. Journal of Education, Health and Sport. 2015;5(6):95-114. ISSN 2391-8306. DOI 10.5281/zenodo.18391 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A95-114 https://pbn.nauka.gov.pl/works/564123 http://dx.doi.org/10.5281/zenodo.18391 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 05.06.2015.   МОРФОЛОГІЧНІ ОСОБЛИВОСТІ БАЗАЛЬНОЇ МЕМБРАНИ БАГАТОШАРОВОГО ПЛОСКОГО ЕПІТЕЛІЮ І ПІДЛЯГАЮЧОЇ СТРОМИ ПРИ ЦЕРВІКАЛЬНИХ ІНТРАЕПІТЕЛІАЛЬНИХ НЕОПЛАЗІЯХ ТА РАКУ ШИЙКИ МАТКИ MORPHOLOGICAL FEATURES OF BASAL MEMBRANE OF STRATIFIED SQUAMOUS EPITHELIUM AND UNDERLYING STROMA IN CERVICAL INTRAEPITHELIAL NEOPLASIAS AND CANCER OF THE UTERINE CERVIX   О. М. Плітень O. N. Pliten   Харківський національний медичний університет Kharkiv National Medical University   Abstract. The article presents the morphological features of the basal membrane of stratified squamous epithelium and underlying stroma in cervical intraepithelial neoplasias and cancer of the uterine cervix which were investigated by routine histological, histochemical and immunohistochemical methods. The present study indicated that as stages of carcinogenesis progress changes in the stromal-vascular component and in the basal membrane of the epithelium occur that has an important role in the differential diagnosis of the stages of carcinogenesis of the uterine cervix. Key words: uterine cervix, cervical intraepithelial neoplasias, cancer, stratified squamous epithelium, basal membrane, stroma, morphology.   Резюме. У роботі розглянуті морфологічні особливості базальної мембрани багатошарового плоского епітелію і підлягаючої строми при цервікальних інтраепітеліальних неоплазіях та раку шийки матки, які були досліджені за допомогою рутинних гістологічних, гістохімічних і імуногістохімічних методів. Дослідження показало, що у міру поважчання стадії канцерогенезу відбуваються зміни стромально-судинного компоненту і базальної мембрани епітелію. Виявлені зміни мають важливу роль у диференціальній діагностиці стадій канцерогенезу у шийці матки. Ключові слова: шийка матки, цервікальні інтраепітеліальні неоплазії, рак, багатошаровий плоский епітелії, базальна мембрана, строма, морфологія.   Резюме. МОРФОЛОГИЧЕСКИЕ ОСОБЕННОСТИ БАЗАЛЬНОЙ МЕМБРАНЫ МНОГОСЛОЙНОГО ПЛОСКОГО ЭПИТЕЛИЯ И ПОДЛЕЖАЩЕЙ СТРОМЫ ПРИ ЦЕРВИКАЛЬНЫХ ИНТРАЭПИТЕЛИАЛЬНЫХ НЕОПЛАЗИЯХ И РАКЕ ШЕЙКИ МАТКИ. В работе рассмотрены морфологические особенности базальной мембраны многослойного плоского эпителия и подлежащей стромы при цервикальных интраэпителиальных неоплазиях и раке шейки матки, которые были исследованы с помощью рутинных гистологических, гистохимических и иммуногистохимических методов. Исследование показало, что по мере утяжеления стадии канцерогенеза происходят изменения в стромально-сосудистом компоненте и в базальной мембране эпителия, что играет важную роль в дифференциальной диагностике стадий канцерогенеза в шейке матки. Ключевые слова: шейка матки, цервикальные интраэпителиальные неоплазии, рак, многослойный плоский эпителии, базальная мембрана, строма, морфология.